The Graduate (1967) - Mike Nichols; Daniels, William, 1927-; Anne Bancroft; Dustin Hoffman; Katharine Ross (USA Embassy Pictures Corporation, 2005)
The action is mainly seen through the eyes of Benjamin Braddock (Dustin Hoffman), a confused twenty-one year old, who is worried about his future but who does not simply want to follow the commercial path of his affluent family and their friends. His life becomes complicated when he is embroiled in an affair with an older woman, Mrs. Robinson (Anne Bancroft), the wife of his father's business partner. It becomes impossible when he falls in love with Mrs. Robinson's daughter, Elaine (Katharine Ross).
Recent college graduate Benjamin Braddock is trapped into an affair with Mrs. Robinson, who happens to be the wife of his father's business partner and then finds himself falling in love with her teenage daughter, Elaine.
Charles Webb
Language(s): English, Turkish Subtitle(s): English, Turkish
Keywords: Drama